Using isotopes for dating and residence time of groundwater in an aquifer, a case study at Al-Najaf, Middle Iraq - Arshad Al-Enezy; Mohanad Al-Owaidi; Mohammed Hussein (Kuwait Journal of Science)
Groundwater is the main source of sustaining life in the Najaf Desert that helps sustain human and animals’ lives. The aquifer of the Dammam Formation is considered the main source of groundwater in the study area. The isotope elements have been used as a geochemical indicator to determine the age, direction of flow and the effect of rainwater of this area. The values of stable isotopes δ18O and δ2H range between -2.56‰ to -1.99‰, and between 7.12‰ to -4.84‰ with an average of -2.32‰ and -6.20‰ in rainfall respectively. Their values range from -3.26‰ to -2.01‰ for δ18O, and from -27.00‰ to -16.21‰ for δ2H with an average of -2.70‰ and - 22.27‰ in the Dammam groundwater respectively. The groundwater is old and does not mix with new water, because tritium has not been not detected. Furthermore, the δ18O and δ2H values show that the rainwater, which feeds the aquifer does not come from the continental lands. They represent a humid and cold climate, as well as a considerable amount of rainfall in the past. Analyses of 14C indicate that the groundwater dates back to approximately 4176 years ago. The groundwater is moving from the west and southwest directions to the north and northeast directions.